Psychometric Properties and Validation of the Positive and Negative Suicide Ideation (PANSI) Inventory in an Outpatient Clinical Population in Malaysia - Sinniah, Aishvarya; Oei, T.P.S.; Chinna, Karuthan; Shah, S.A.; Maniam, T.; Subramaniam, Ponnusamy (Frontiers Media, 2015)
The PANSI is a measure designed to assess the risk and protective factors related to suicidal behaviors. The present study evaluated the psychometric properties and factor structure of the Positive and Negative Suicide Ideation (PANSI) Inventory in a sample of clinical outpatients at a major hospital in Malaysia. In this study, 283 psychiatric patients and 200 medical (non psychiatric) patients participated. All the patients completed the PANSI and seven other self-report instruments. Confirmative factor analysis supported the 2-factor oblique model. The internal consistency of the two subscales of PANSI-Negative and the PANSI-Positive were 0.93 and 0.84, respectively. In testing construct validity, PANSI showed sizable correlation with the other seven scales. Criterion validity was supported by scores on PANSI which differentiated psychiatric patients from medical patients. Logistic regression analyses showed PANSI can be used to classify the patients into suicidal or non suicidal. The PANSI is a reliable and valid instrument to measure the severity of suicidal ideation among clinical outpatients in Malaysia.